2005
DOI: 10.1585/jspf.81.204
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Radio Frequency Inductive Discharges in Near Atmospheric Pressure Using Immittance Conversion Topology

Abstract: A radio frequency (rf) inductive discharge in atmospheric pressure range requires high voltage in the initial startup phase and high power during the steady state sustainment phase. It is, therefore, necessary to inject high rf power into the plasma ensuring the maximum use of the power source, especially where the rf power is limited. In order to inject the maximum possible rf power into the plasma with a moderate rf power source of few kilowatts range, we employ the immittance conversion topology by converti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Radio frequency inductive plasmas were generated in a device known as a RIP (RF Inverter Plasma torch) [12][13][14][15][16][17]. The plasmas were sustained in a cylindrical Pyrex glass chamber having an inner diameter of 70 mm and length of 200 mm by applying a rf power from a static induction transistor (SIT) inverter power source.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radio frequency inductive plasmas were generated in a device known as a RIP (RF Inverter Plasma torch) [12][13][14][15][16][17]. The plasmas were sustained in a cylindrical Pyrex glass chamber having an inner diameter of 70 mm and length of 200 mm by applying a rf power from a static induction transistor (SIT) inverter power source.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, radio frequency rf-inductive plasmas in the atmospheric pressure range have been developed using a author's e-mail: ohno@ees.nagoya-u.ac.jp static induction transistor (SIT) inverter power source [12][13][14][15][16][17]. However, in order to use these rf-inductive plasmas in industrial and environmental applications, it is necessary to measure the plasma parameters (electron temperature, T e , and electron density, n e ) as a way to elucidate the quality of the generated plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for capacitively coupled plasmas, the plasma efficiency decreases as the power increases and the sheath voltage increases. Therefore, it is necessary to design dynamically variable components, preferably with automated electromechanical drives for tuning vacuum variable capacitors, as well as to have special design consideration for the power inverter section [64]. Due to the reduced loss of electrons in ICPs, the plasma densities attained in these are much higher than those in CCPs.…”
Section: Description Of Icps and Comparison With Other Plasma Applicamentioning
confidence: 99%
“…H-mode was sustained by the electromagnetic field [13]. M. A. Razzak et al [14] reported that plasma in E-mode occurred ring-shaped nearly around the discharge chamber closing to the inductive electrode. However, the H-mode was in the form of the volumetric induction plasma.…”
Section: Introductionmentioning
confidence: 99%